A study of lipid profile in young smokers and non-smokers - Sahu, Rahul; Singh, Reena; Giri, Richa (International Journal of Advances in Medicine, 2022)
Background: A prospective study was carried out to find the variations in lipid profile in smokers when compared to non-smokers. The aim was to study the alterations in lipid profile in terms of severity of smoking. Methods: This study was carried out among 198 patients who attended medicine OPD of LLR hospital GSVM medical college Kanpur. The population was divided into 98 non-smokers and 100 smokers. The smokers were further divided into 3 groups depending on the intensity of smoking. Results: Out of 100 patients in the present study the number of subjects in mild, moderate and high smokers’ group were 33 (33%), 33 (33%), 34 (34%) respectively. Smokers had higher total cholesterol, plasma triglycerides, serum low density lipoprotein (LDL), serum very low-density lipoprotein (VLDL) and lower levels of serum high density lipoprotein (HDL) compared to non-smokers which was statistically significant. Conclusions: Increase in total cholesterol, triglycerides, LDL and VLDL were found in smokers of all age groups. Whereas HDL values showed inverse relationship. These changes were directly proportional to the severity of smoking. So, Tobacco smoking is associated with dyslipidemia which is atherogenic in nature.